Fight against Childhood Malnutrition - A Must Win Battle - Shakeel Ahmed (Journal of Bahria University Medical and Dental College)
Child growth is internationally recognized as an important indicator of nutritional status and health of the nation by which the nutritional status of the population can be assessed. Nutritional imbalance results in under nutrition (underweight, wasting and stunting) and over nutrition (overweight & obesity).